ANALISIS PENGARUH JARINGAN USAHA DAN INOVASI TERHADAP KINERJA UMKM - Hendriyanto, Asepta (Jurnal Ilmu Manajemen dan Akuntansi Terapan (JIMAT), 2015)
The development of a business unit can be affected by a variety offactors, both internal and external company factors. The purpose of thisresearch is to know the influence of the business network, and productinnovation against the performance of micro, small and medium enterprises.The research type is explanatory research. The population was 162 unitsfrom small and medium metal industries in Boyolali District with 85sample taken using disproportionate stratified random sampling and simplerandom sampling. Data collection using the questionnaire. Data analysisusing linear regression analysis. The results showed that the businessnetwork, and product innovation are jointly undertaking a positive andsignificant effect against performance of micro, small and mediumenterprises. Researchers suggest that UMKM constantly enhance cooperationwith various parties to build wider business network, andimprove productinnovation so that UMKM can continue to thrive in the midst of the currentcompetition.